Multiple immune-related adverse events secondary to checkpoint inhibitor therapy in patients with advanced cancer: association with treatment effectiveness - Olsson Ladjevardi, Cecilia; Koliadi, Anthoula; Rydén, Viktoria; El-Naggar, Ali Inan; Digkas, Evangelos; Valachis, Antonios; Ullenhag, Gustav J. (Frontiers in Oncology, 2024)
Introduction: Checkpoint inhibitors (CPI) are widely used in cancer treatment with a potential of causing immune-related adverse events (IRAEs). Several studies have reported a positive correlation between development of IRAEs and improved survival outcome.However, few studies have focused on the potential role of multiple IRAEs on treatment effectiveness. This study aimed at investigating the association between multiple IRAEs and treatment effectiveness in terms of progression-free survival (PFS) and overall survival (OS) in advanced cancer patients.We performed a retrospective cohort study at three Swedish centers. All patients (n=600) treated with PD-L1 or PD-1 inhibitor, in monotherapy or in combination for advanced cancer between January 2017 and December 2021 were included. Multiple IRAEs were defined as IRAEs involving more than one organ system either simultaneously or sequentially. Time-depending Cox-regression model to mitigate the risk for immortal time bias (ITB) was applied.The major tumor types were non-small cell lung cancer (205 patients; 34.2%) and malignant melanoma (196 patients; 32.7%). Of all patients,32.8% developed single IRAE and 16.2% multiple IRAEs. Patients with multiple IRAEs showed significantly improved PFS (Hazard Ratio, HR=0.78 95% Confidence Interval, CI: 0.57-0.98) and OS (HR=0.65 95% CI: 0.44-0.95) compared to patients with single IRAE or no IRAE (HR=0.46 95% CI:0.34-0.62 for PFS vs HR=0.41 95% CI: 0.28-0.60 for OS).In conclusion, our data supports a stronger association between development of multiple as opposed to single IRAEs and clinical effectiveness in advanced cancer patients treated with CPIs.